ENTEROCOCCUS SPP. INFECTIONS AT THE HOSPITAL FOR TROPICAL DISEASES (2021 – 2023): EPIDEMIOLOGICAL CHARACTERISTICS, PATHOGENS, AND VANCOMYCIN RESISTANCE (Vietnam Journal of Community Medicine, 2026)
Methods: A descriptive cross-sectional study (retrospective and prospective) was conducted on 216 patients with Enterococcus spp. infections treated at the Hospital for Tropical Diseases from January 2021 to August 2023. Factors associated with vancomycin-resistant Enterococcus spp. (VRE) infection were identified using univariate and multivariate logistic regression models.Results: Healthcare-associated infections due to Enterococcus spp. accounted for 87%, significantly outnumbering community-acquired infections, with the urinary tract being the most common infection site. E. faecium was the most prevalent pathogen (63%), followed by E. faecalis (36%). The overall rate of VRE infection was 34.3%, while E. faecium specifically showed a vancomycin resistance rate of 45.8%. Multivariate analysis revealed that patients aged ≥ 60 years had a significantly higher risk of VRE infection compared to those aged
Keywords: Enterococcus spp.; VRE; vancomycin resistance; antibiotic resistance; nosocomial infection; healthcare-associated infection